Lab safety reimagined: bridging theory and practice through task-based assessment - Firus Khan, Al’aina Yuhainis; Md Shamsudin, Nurshamshida; Syed Aris, Sharipah Ruzaina (2025)
Preservice science teachers often struggle to understand and apply the HIRARC framework (Hazard Identification, Risk Assessment, and Risk Control) because traditional teaching focuses heavily on theory with limited real-life laboratory practice. This gap hinders their ability to apply safety concepts effectively. This innovation presents a task-based assessment framework that engages students in authentic problem-solving by addressing safety gaps in a newly relocated laboratory without formal safety protocols. The initiative is packaged into a teaching pack containing project guidelines, assessment rubrics, tasks, and sample outputs. Students worked in groups for one month to tackle real laboratory safety issues. They collaborated with the lab assistant and coordinator to ensure practical and relevant solutions. Tasks included creating safety posters, drafting lab rules and regulations, labelling equipment and chemicals, developing inventory systems, writing standard operating procedures, and compiling a comprehensive safety manual. Outputs were showcased and evaluated during the Occupational Safety and Health (OSH) Day. Students showed improvement in understanding and applying HIRARC principles, and their work contributed directly to long-term improvements in lab safety infrastructure. This task-based approach bridges theory and practice, encouraging meaningful, ethical problem-solving. It aligns with values-based education principles such as responsibility, integrity, collaboration, and sustainability, while developing key competencies in critical thinking, problem solving, and teamwork. Several student-produced materials are now in active use, forming part of the lab’s permanent safety system. This scalable model offers a practical and sustainable strategy for embedding scientific safety skills in teacher education.